2018
DOI: 10.1136/bjsports-2017-098417
|View full text |Cite
|
Sign up to set email alerts
|

On average, a professional rugby union player is more likely than not to sustain a concussion after 25 matches

Abstract: Concussion incidence increased, while severity remained unchanged, during the 4 years of this study. Playing more than 25 matches in the 2015/2016 season meant that sustaining concussion was more likely than not sustaining concussion. The 38% greater injury risk after concussive injury (compared with non-concussive injury) suggests return to play protocols warrant investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 29 publications
3
46
1
Order By: Relevance
“… 14 31 Some investigators have found a link between higher injury rates in heavier players, while others have not. 22 31–33 Interestingly, although not a universal finding, one study has found centres and hookers, the players we have identified as increasing mass disproportionately since professionalism, have the greatest risk of injury. 34 In another study, again midfield backs (centres) had the greatest absence through injury 31 ; the reason cited was high-speed tackles, which brings us back to Newton’s laws of motion and the forces involved when big people run very fast into each other.…”
Section: Discussionmentioning
confidence: 81%
“… 14 31 Some investigators have found a link between higher injury rates in heavier players, while others have not. 22 31–33 Interestingly, although not a universal finding, one study has found centres and hookers, the players we have identified as increasing mass disproportionately since professionalism, have the greatest risk of injury. 34 In another study, again midfield backs (centres) had the greatest absence through injury 31 ; the reason cited was high-speed tackles, which brings us back to Newton’s laws of motion and the forces involved when big people run very fast into each other.…”
Section: Discussionmentioning
confidence: 81%
“…This study also reiterated certain factors associated with a student having sustained a concussion in their lifetime. Male students, those who played contact sports, and students who played 2 seasons of sports at school (ie, more exposure) were more likely to report a concussion in their lifetime than other students.…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies within each sport varied, with 31 studies in football/soccer [4,25,30,, 13 in rugby (two rugby sevens, eleven rugby union) [2,27,[65][66][67][68][69][70][71][72][73][74][75], five in athletics [76][77][78][79][80], one in Olympic multi-event [81] and one in cricket [70] (Table 2). There were no studies from aquatic sports, horseracing or tennis.…”
Section: Orchard Et Al 2016 [15]mentioning
confidence: 99%
“…There was a wide range in the number of participants included in the data collection, from 36 athletes [39] to 9672 athletes [81], whilst nine studies only reported the number of teams without providing the number of individual athletes that participated [37,42,44,47,51,70]. Only ten studies reported the number of athletes sustaining the total number of injuries [30,41,47,50,56,65,70,72,75], and two studies reported the proportion of players who sustained more than one injury [27,30]. The majority of studies (n = 37) used a time-loss definition for injury, five used a medical attention definition, five used a medical attention and time-loss definition and four used an all-encompassing definition.…”
Section: Orchard Et Al 2016 [15]mentioning
confidence: 99%